2018
DOI: 10.1016/j.oceaneng.2018.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Non-parametric dynamic system identification of ships using multi-output Gaussian Processes

Abstract: Non-parametric system identification with Gaussian Processes for underwater vehicles is explored in this research with the purpose of modelling autonomous underwater vehicle (AUV) dynamics with low amount of data. Multi-output Gaussian processes and its aptitude to model the dynamic system of an underactuated AUV without losing the relationships between tied outputs is used. The simulation of a first-principles model of a Remus 100 AUV is employed to capture data for the training and validation of the multi-ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The trajectory-tracking experience chosen in this work consists in evaluating the performance of a LQR based controller for tracking position zig-zag and circular trajectories in the horizontal plane, as they are usually employed by researchers in this kind experiments with ship model [12], [13], [14], [15], for the horizontal plane. To these ends, a linear model for the system must be computed.…”
Section: Methodsmentioning
confidence: 99%
“…The trajectory-tracking experience chosen in this work consists in evaluating the performance of a LQR based controller for tracking position zig-zag and circular trajectories in the horizontal plane, as they are usually employed by researchers in this kind experiments with ship model [12], [13], [14], [15], for the horizontal plane. To these ends, a linear model for the system must be computed.…”
Section: Methodsmentioning
confidence: 99%
“…The kernel methods overcome these problems based on statistical learning theory [35]. The kernel methods, such as SVM [28], the Gaussian process (GP) [36], locally weighted learning (LWL) [37] and kernel ridge regression confidence machine [38], are used for identifying the marine dynamic model. Among them, the GP have stronger robustness and generalization with a priori introduction from Bayesian perspective than other methods.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to parametric gray-box modeling, ship dynamic models based on conjugate and semiconjugate Bayesian regression (ScBR) are adopted to estimate the hydrodynamic parameters in our previous work [44]. For the black-box modeling, Ariza Ramirez et al [36] used multioutput GPs to identify the ship dynamic system and showed that the GP scheme has better generalization than recurrent neural network (RNN). A series of Bayesian methods is used to quantify the extremal responses of a floating production storage and offloading (FPSO) vessel in [45].…”
Section: Introductionmentioning
confidence: 99%
“…Before designing the controller, it is necessary to identify the system dynamics. This process requires using an excitation and storing the input and output data, in order to obtain a model that can correctly describe the system behavior [2]. In this context, identification techniques arise, which use statistical methods to design mathematical models from experimental data of a process [3,4].…”
Section: Introductionmentioning
confidence: 99%